Targeted mass spectrometry analysis of neutrophil-derived proteins released during sepsis progression - Malmström, Erik; Davidova, Alzbeta; Mörgelin, Matthias; Linder, Adam; Larsen, Michael; Qvortrup, Klaus; Nordenfelt, Pontus; Shannon, Oonagh; Dzupova, Olga; Holub, Michal; Malmström, Johan; Herwald, Heiko (Thrombosis and Haemostasis, 2014)
Early diagnosis of severe infectious diseases is essential for timely implementation of lifesaving therapies. In a search for novel biomarkers in sepsis diagnosis we focused on polymorphonuclear neutrophils (PMNs). Notably, PMNs have their protein cargo readily stored in granules and following systemic stimulation, an immediate increase of neutrophil-borne proteins can be observed into the circulation of sepsis patients. We applied a combination of mass spectrometry (MS) based approaches, LC-MS/MS and selected reaction monitoring (SRM), to characterise and quantify the neutrophil proteome in healthy or disease conditions. With this approach we identified a neutrophil- derived protein abundance pattern in blood plasma consisting of 20 proteins that can be used as a protein signature for severe infectious diseases. Our results also show that SRM is highly sensitive, specific, and reproducible and, thus, a promising technology to study a complex, dynamic and multifactorial disease such as sepsis.
Keywords: Coagulation; infectious diseases; innate immunity; neutrophils; mass spectrometry; proteomics